Subaltern in the Novel Buku Merah Kirayu by Budhi Kurniawan: A Postcolonial Study of Spivak (Universitas Pamulang, 2024)
This study aims to describe the forms of domination by hegemonic groups over the subaltern and how the subaltern is narrated in the novel Buku Merah Kirayu. Additionally, the study seeks to identify the author’s perspective from a sociological standpoint. The object of analysis in this research is the novel Buku Merah Kirayu. Primary data sources are derived from the text of the novel, while secondary data sources include scholarly articles and news articles relevant to the research topic.The data is analyzed using Spivak's theory of subalternity. According to Spivak, the subaltern is defined as a group that is not only marginalized but also lacks a voice in dominant power structures. The analysis is conducted in two stages: textual analysis and an examination of the sociological aspects of the author. The results show that the narrative about the subaltern in the novel Buku Merah Kirayu is constructed in the prologue, which contains the author's critique of a political system that fails to serve the interests of the people, particularly marginalized groups whose voices are not heard. Furthermore, subalternity is also depicted through the character Ilena, who represents the victim (subaltern), and the character Daruna, who exercises dominance and oppression (hegemon). From a sociological perspective, the author’s stance shows solidarity with the subaltern, aligns with progressive social groups, and positions themselves as an advocate against the oppression of subaltern groups.